A case study of gesture-based games in enhancing the fine motor skills and recognition of children with autism. Issue 8 (17th November 2018) - Cai, Su; Zhu, Gaoxia; Wu, Ying-Tien; Liu, Enrui; Hu, Xiaoyi
ABSTRACT: Children with Autism Spectrum Disorder (ASD) perform poorly in complex fine motor skills and recognition, and they have difficulties in learning complex and multistep motor skills. Gestures-based games, which enable users to get timely feedback, to learn from failure, to engage in games at every moment, and to interact with computers intuitively have become promising tools. However, relevant empirical research on using gesture-based games to assist the learning of children with ASD is limited. With a case study method, we aim to examine the effects of using gesture-based games on the learning of children with ASD. Two gesture-based matching games were developed to improve the performance of children with ASD with respect to fine motor skills and recognition, and three young children with ASD participated in a three-week experiment. By comparing the participants' performance before and after the treatment, we found that the participants' performance in playing the gesture-based games improved greatly during the intervention, and intervention helped improve their performance regarding fine motor skills and recognition. Also, they were able to transfer the rules and skills they had learnt from the first game to completing the tasks in the second game. The findings above suggest the usefulness of using gesture-based games in assisting the learning of children with ASD. Some suggestions and implications for the development of the gesture-based games and future work are also discussed.